Unveiling the neuropathology tumour landscape: 10-year statistical analysis with global comparison – Single centre experience - Zdravkovski, Panche; Ilievski, Boro; Rendevski, Vladimir; CHaparoski, Aleksandar; Filipche, Venko; Zupanoski, Aleksandar; Gavrilovska dimovska, Aleksandra; SHuntov, Blagoj; Stolevski, Vlado; Stojkovski, Igor; Lazareska, Menka; Mihajlovska Rendevska, Ana; et al. (Macedonian Academy of Sciences and Arts, 2023)
Introduction: Central nervous system (CNS) tumours represent a significant public health issue worldwide, and their incidence and distribution vary across different populations. Although studies on CNS tumours have been conducted in various countries, there is a lack of information regarding their patterns in Macedonia. Therefore, this study is aimed at investigating the distribution, histopathological types and subtypes and demographic features of CNS tumours in our country. Materials and Methods: A cross sectional study was conducted using the electronic database of the Institute of Pathology – Medical Faculty, University “Ss. Cyril and Methodius” in Skopje which contains data from 3286 received and analysed surgical specimens, mainly from the University Clinic of Neurosurgery in Skopje, and a smaller number of surgical specimens from the University Surgical Centre “St. Naum Ohridski” in Skopje between 2012 and 2022. The collected and analysed data includes patient age, sex and histopathological types and subtypes of the tumours. Results: The majority of CNS tumours were diagnosed in adults aged between 50-70, with a male to female ratio of 1.5:1. The most common location of the tumours was the cerebrum, followed by the pituitary gland and cerebellum. The most frequent histological groups were gliomas, with glioblastoma as the most common diagnosis, followed by meningiomas. Conclusion: Following a detailed and thorough review of the CNS tumours in our study, we can conclude that the R. of Macedonia follows global statistics and trends regarding brain tumours.
Keywords: neuropathology; CNS tumours; prevalence; analysis; global trends